Application of Professional Zakat for State Civil Apparatus (Case Study of BAZNAS Sinjai Regency) - Muin, Rahmawati; Taqiyuddin BN, Andi Muh.; Lutfi, Mukhtar; Bakry, Muammar Muh.; Musyahid, Achmad (PT FORMOSA CENDEKIA GLOBAL, 2023)
The main problem of this research is how is the application of professional zakat for State Civil Apparatus (case study of BAZNAS, Sinjai Regency)? The main problem is then broken down into sub-problems or research questions, namely: What is the practice of managing professional zakat for ASN by the Sinjai Regency National Zakat Amil Agency (BAZNAS) within the Regency Regional Government? Sinjai. This type of research is classified as qualitative with the research approach used being: sociological. The informant in this research was the Chairman of BAZNAS district. Sinjai, Deputy Chair I, II, IV BAZNAS Kab. Sinjai, 4 professional zakat muzakki, and Head of the District's Regional Finance and Assets Agency. Sinjai. Furthermore, the data collection methods used were observation, interviews and documentation. Then, data processing and analysis techniques are carried out through three stages, namely: data collection, data reduction, data presentation, and conclusion drawing